A call for knowledge and awareness with reference to organ donation among nursing students - ABM Tofazzal Hossain; Shaila Kabir; Liew, Constance Sat Lin; Fairrul Kadir; M Tanvir Hossain Parash; Sadia Choudhury Shimmi; Mohd Yusof Ibrahim; Mohammad Saffree Jeffree; Ehab Helmy Abdel Malek Fahmy; Symeon Mandrinos (Malaysian Journal of Medicine and Health Sciences, 2020)
Role of nurses is very important in raising awareness, motivation level and increasing rate of organ donation subsequently. There are many studies on critical care nurses’ roles and education affect organ donation. Methods: A narrative literature review article of published research. Twelve published articles from ten different countries were found using different renowned online search engines. Results: Knowledge about organ donation among nursing students almost all over the world is inadequate than expectation and requirement in respective country. Marlene R et al showed that scores on the knowledge, attitudes, and beliefs subscales were positively cor¬related with the number of requests for tissue and organs and consents obtained (0.76); and consents obtained for tissues and consents obtained for organs (0.72). Professional education was indicated in 43% of nurses surpassing family beliefs, religion and mass media. The cognitive part (knowledge) is directly depends on non-cognitive (Aware-ness and Attitude). Findings from almost all articles suggest the need of adding organ donation topic in the nursing and medical curriculum to prepare competent nurses and health care providers for future. Conclusion: This study suggests that there is a need to integrate organ donation aspects into the educational program to prepare nurses for their roles in organ and tissue procurement as well as awareness among policy makers in this regard for the well-be¬ing of our patients.